2022
DOI: 10.1097/j.pain.0000000000002758
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased analysis of the dorsal root ganglion after peripheral nerve injury: no neuronal loss, no gliosis, but satellite glial cell plasticity

Abstract: Supplemental Digital Content is Available in the Text.Deep learning-based analysis of large-scale bioimages of the dorsal root ganglion after nerve injury reveals satellite glial cell plasticity but no loss of sensory neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…Avulsed DRG were collected during nerve reconstruction surgery and analyzed by immunohistochemistry, large-scale tile microscopy, human DRG-adapted deep learning-based algorithms, 23 and new concepts for quantitative assessment of the different cell types close to the neuron-satellite-glia unit. 11 Our data document that patients suffering from plexus injury can be categorized into two groups: patients with total loss or patients with complete preservation of the multicellular DRG entity.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Avulsed DRG were collected during nerve reconstruction surgery and analyzed by immunohistochemistry, large-scale tile microscopy, human DRG-adapted deep learning-based algorithms, 23 and new concepts for quantitative assessment of the different cell types close to the neuron-satellite-glia unit. 11 Our data document that patients suffering from plexus injury can be categorized into two groups: patients with total loss or patients with complete preservation of the multicellular DRG entity.…”
Section: Introductionmentioning
confidence: 79%
“…Pixel resolution was 0.454 μm. Objective bioimage analysis was performed using deepflash2 31 as described recently, 11, 23 with some modifications. Image feature annotation was performed on 10 exemplary sections marked by neurofilament (NF) by three experts using the QuPath software (Bankhead et al 2017, RRID:SCR_018257).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SGCs, which share biological properties with astrocytes in the CNS ( Ceruti, 2021 ), are activated during neuroinflammation in the PNS ( Matsuda et al, 2019 ). Previous studies have reported that nerve injury or persistent inflammation not only causes neuronal changes leading to peripheral sensitization but also results in activation of SGCs in the DRG ( Blum et al, 2014 ; Schulte et al, 2022 ). It is generally known that SGCs overactivation contributes to peripheral neuroinflammation and pathological pain via SGC-neuron interactions.…”
Section: Discussionmentioning
confidence: 99%